Research and productivity: Manufacturing companies in cities have an advantage - Heike Belitz; Alexander Schiersch (DIW Weekly Report, 2018)
Companies invest in research and development (R&D) to safeguard their competitive ability and increase productivity. Using extensive company data for Germany, the study shows that manufacturing companies that engage in R&D activities and that are located in a central urban agglomeration are especially productive. They additionally benefit from knowledge created by R&D activities of other companies and public research. However, the regional research systems in major urban regions are very different. These differences require tailored support by research and technology policy for the development of regional research and innovation systems on a region-by-region basis. The goal should be to reinforce the regional transfer of knowledge among companies, universities, and non-university research institutes. Regional differences must be taken into account when devising policy because uniform programs on the federal level will have different effects depending on the research region.
Keywords: D24; O33; R11; R15; 330; productivity; regions; R&D